2021
DOI: 10.1177/23197145211053400
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Merger and Acquisition on Financial Performance: Evidence from Construction and Real Estate Industry of India

Abstract: This article aims to examine the impact of mergers and acquisitions (M&A) on the financial performance of the construction and real estate industry, using the broad spectrum of financial ratios. The period of study is from 2011 to 2020, and paired t-test methodology has been used. It is hypothesized that there is a significant difference in the pre-M&A period and post-M&A period. The study findings conclude that profitability ratio and liquidity ratio have improved significantly, whereas leverage r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
(73 reference statements)
2
8
0
Order By: Relevance
“…The results of this study support that the performance subsequent of mergers is not significantly different for the merged companies and is similar with other past studies (Cosh et al, 1980;Chatterjee & Meeks, 1996;Healy et al, 1992;Ghosh, 2001;Sharma & Ho, 2002;Al-Hroot, 2016;Pantelidis et al, 2018). In addition, these results are in contrast with several other past studies that found an improvement or value creation after mergers (Utton, 1974;Meeks, 1977;Kumar, 1984;Mueller, 1985;Lang et al, 1989;Netter et al, 2011;Dargenidou et al, 2016;Alhenawi & Stilwell, 2017;Gupta et al, 2021) or a decrease in business performance, profitability or additional leverage for the merged companies (Dickerson et al, 1997;Pawaskar, 2001;Yeh & Hoshino, 2002;Harford et al, 2009;Bhabra & Huang, 2013;Jandik & Lallemand, 2014;Harrison et al, 2014). Furthermore, almost the same results are received using the median for the comparisons with Mann-Whitney tests (as are tabulated in Table 5b).…”
Section: Results For Research Sample and Control Samplesupporting
confidence: 91%
See 2 more Smart Citations
“…The results of this study support that the performance subsequent of mergers is not significantly different for the merged companies and is similar with other past studies (Cosh et al, 1980;Chatterjee & Meeks, 1996;Healy et al, 1992;Ghosh, 2001;Sharma & Ho, 2002;Al-Hroot, 2016;Pantelidis et al, 2018). In addition, these results are in contrast with several other past studies that found an improvement or value creation after mergers (Utton, 1974;Meeks, 1977;Kumar, 1984;Mueller, 1985;Lang et al, 1989;Netter et al, 2011;Dargenidou et al, 2016;Alhenawi & Stilwell, 2017;Gupta et al, 2021) or a decrease in business performance, profitability or additional leverage for the merged companies (Dickerson et al, 1997;Pawaskar, 2001;Yeh & Hoshino, 2002;Harford et al, 2009;Bhabra & Huang, 2013;Jandik & Lallemand, 2014;Harrison et al, 2014). Furthermore, almost the same results are received using the median for the comparisons with Mann-Whitney tests (as are tabulated in Table 5b).…”
Section: Results For Research Sample and Control Samplesupporting
confidence: 91%
“…The mean from the sum of each quantitative variable is computed and further compared with t-tests in different subsamples of pre-and post-merger period. The mean of a data set is widely adopted in the relevant literature of depicturing the impact from mergers and acquisitions (Al-Hroot, 2016;Pantelidis et al, 2018;Aggarwal & Garg, 2019;Gupta et al, 2021;Lois et al, 2021). However, in order to avoid mean's various limitations and verify the received results from mean's analysis, the study computes the median too from the sum of each accounting measures and financial ratio and employs a non-parametric test, Mann-Whitney test, for median comparisons (Mueller, 1980;Cosh et al, 1980;Sharma & Ho, 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, in 2022, Khuntaweetep and Koowattanatianchai created an econometric model for strategic planning and ROE forecasting of real estate development companies in Thailand. Even more recently, in 2023, Gupta et al . examined the impact of mergers and acquisitions on the financial performance of the construction and real estate industry using numerous ratios.…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…The primary goal of the study was to examine how mergers from 2006 to 2012 affected the performance of the bidding firm. The selected sample revealed a reduction in profitability, demonstrating that not all mergers and acquisitions boost performance and that other ways of expansion, such as consolidation and reorganization, should be explored (Bijoy Gupta, 2017). In his investigation into how mergers and acquisitions affect banks' financial health (a survey of commercial banks in Kenya), Bijoy Gupta (2017) found that the majority of firms merge in order to increase their effectiveness by increasing their market share.…”
Section: Literature Reviewmentioning
confidence: 99%